Implementation of Topsis Method In Web Based System Recommendations For Students Laptop Selection (Case Study: Bhinneka.com) - Adhi Kusnadi; Edwin Kurniawan (Universitas Multimedia Nusantara, 2017)
Computer needs at work are very helpful and make easier for human to complete his work. The usageof laptops growing rapidly with increasing mobility of the community who uses laptop to run the activities. In addition, laptop continues to update its technology with the variation of the specification so that it can attract the interest of consumers, especially for students, but the variety of laptops is confusing for some users to choose. Based on a survey that has been done to the students, it concluded that laptop is 80% more interesting than desktop computer. Some students really need a recommendation system for choosing alaptop. In making a recommendation system, using TOPSIS method is the recommended one because the concept is simple, easy to understand, efficient, and have the ability to measure the relative performance of alternatives decision. According to the implementation, the recommendation system with TOPSIS method has 70% accuracy rate. Index Terms—System Recommendation, TOPSIS, Laptop, REFERENCES [1] Hendra, dkk. 2007. “Keluhan Kesehatan pada Penggunaan Laptop pada Mahasiswa FKM UI”. (pdf). Depok: Universitas Indonesia. [2] Paays, N. 2013. Rancang Bangun Meja Laptop Yang Adjustable Berdasarkan Aspek Ergonomi. Pontianak: Universitas Tanjungpura. [3] Iqbal, M. 2014. Perilaku Pembelian Laptop Oleh Mahasiswa Strata 1 Universitas Brawijaya Malang. S1 thesis. Malang: Universitas Brawijaya. [4] Setiawan, H. 2014. Rancang Bangun Aplikasi Rekomendasi Pembelian Laptop Dengan Metode Fuzzy Database Tahani Model Berbasis Web (Studi Kasus: Toko Ricky Komputer). S1 thesis. Tangerang: Universitas Multimedia Nusantara. [5] Fitriani, S. A. 2014. Perbandingan Metode Weighted Product dengan Metode Technique for Order Preference by Similarity to Ideal Solution dalam Pendukung Keputusan Perekruten Siswa/Mahasiswa Praktek Kerja Lapangan. S1 thesis. Bandung : Universitas Pendidikan Indonesia. [6] Buaton, R.2014. 15 Metode Menyelesaikan Data Mining, Sistem Pakar, dan Sistem Pendukung Keputusan (.pdf). Medan. [7] Salehah, A. 2014. Penerapan TOPSIS (Technique for Order Preference by Similarity to Ideal Solution) Untuk Seleksi Penerimaan Beasiswa (Studi Kasus Pendaftar Beasiswa dari Fakultas MIPA di Universitas Brawijaya). S1 thesis. Malang : Universitas Brawijaya. [8] Gay, L.R. dan Diehl, P.L. (1992), Research Methods for Business and. Management, MacMillan Publishing Company, New York